2006
DOI: 10.1063/1.2162148
|View full text |Cite
|
Sign up to set email alerts
|

The Faraday effect revisited: General theory

Abstract: This paper is the first in a series revisiting the Faraday effect, or more generally, the theory of electronic quantum transport/optical response in bulk media in the presence of a constant magnetic field. The independent electron approximation is assumed. At zero temperature and zero frequency, if the Fermi energy lies in a spectral gap, we rigorously prove the Widom-Streda formula. For free electrons, the transverse conductivity can be explicitly computed and coincides with the classical result. In the gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Bellissard [10] showed that for discrete mobility gapped systems this definition gives the same value as the double-commutator formula, see also [47]. For unbounded Bloch-Landau Hamiltonians, Streda's formula was recently proved by Cornean, Monaco, and Moscolari [15], see also [17]. We are not aware of similar results on magnetic response for interacting systems.…”
Section: Related Resultsmentioning
confidence: 90%
“…Bellissard [10] showed that for discrete mobility gapped systems this definition gives the same value as the double-commutator formula, see also [47]. For unbounded Bloch-Landau Hamiltonians, Streda's formula was recently proved by Cornean, Monaco, and Moscolari [15], see also [17]. We are not aware of similar results on magnetic response for interacting systems.…”
Section: Related Resultsmentioning
confidence: 90%
“…By adding a positive constant to V , we can take a = −1 uniformly in L 1 and B ∈ [0, 1]. We introduce the transverse component of the conductivity tensor (see [13,29]) as…”
Section: The Main Resultsmentioning
confidence: 99%
“…There are several works using the first principle calculation to evaluate the optical response of carbon nanotubes [21], [22]. The approach used in these works is solving quantum mechanical equations to define electronic and photonic coefficients [23]. However, only incident field is considered in these calculations.…”
Section: Em Scattering Model For Cnt Photovoltaic Devicementioning
confidence: 99%
“…. (23) where J n is a Bessel function of order n and Rg stands for regular. The outgoing cylindrical wave is ψ n (k ρ , k z , r ) = H (1) n (k ρ ρ)e ik z z +inφ (24) where H…”
Section: Appendix a Vector Cylindrical Waves Waveguide Modal Solutiomentioning
confidence: 99%